Case report: Alpelisib-induced Stevens–Johnson syndrome - Kurian, Christine Jane; Desai, Akshay; Rafferty, William; Abou Hussein, Ahmed Kamel (Frontiers in Oncology, 2022)
Background: Alpelisib is a recently approved treatment for hormone receptor positive, HER2 negative, PIK3-mutated advanced breast cancer. It has been associated with alopecia and rash, but there are no documented cases of Stevens Johnson Syndrome (SJS) associated with this drug. Here, we detail the first case of SJS associated with alpelisib. Case Description: Our patient is a 60 year old female with a past medical history of metastatic hormone receptor positive (ER+ 80% and PR+ 1%), HER2 negative metastatic breast cancer who presented with acute odynophagia, fevers and diffuse body rash after receiving her first doses of alpelisib and fulvestrant in the preceding days. She presented to the Emergency Department after developing a whole body rash and severe ulceration of her buccal mucosa. She was started on methylprednisolone with remarkable improvement in symptoms. Conclusion: This case report details the only report of SJS following alpelisib treatment. Immediate cessation of drug and initiation of steroids is the cornerstone of treatment. Patients who experience such side effects will have to be monitored closely for long-term sequela associated with SJS, including cutaneous, ocular, and oral sequela all of which can profoundly affect quality of life for cancer patients.